PROGRAM PEMBINAAN USAHA KERIPIK NENAS DI KECAMATAN TAMBANG - Akbar, Alfitrah; Rusli SD, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This thesis describes a study of the Pineapple Chips Business Development Program in Tambang District. The Pineapple Chips Business Development Program is an activity carried out to try to make things better and solve the problems found in the MSE of pineapple chips in the Tambang District. This study uses a theoretical concept quoting from Adi in Basri (2007: 87), explaining that there are 6 community empowerment processes carried out in the form of programs namely Preparation Phase, Assessment Phase, Alternative planning stage, Action plan formulation stage, Implementation phase and Termination stage. The author uses qualitative research methods by analyzing data descriptively. In collecting research data using interview, observation, and documentation techniques. From the results of this study, it can be seen that the Pineapple Chips Business Development Program created by the Cooperative and UMK Trade Office has not been maximally achieved. There are still work programs that have been planned but not yet implemented.Keywords: Development, Pineapple Chips Business